EFFECT OF CHEMICAL COMPOSITION OF WATER ON THE OXYGEN-18 AND CARBON-13 SIGNATURE PRESERVED IN CRYOGENIC CARBONATES, ARCTIC CANADA: IMPLICATIONS IN PALEOCLIMATIC STUDIES - Lacelle D.; Clark I.D.; Lauriol B. (My University, 2006)
This study examines the δ18O and δ13C composition of cryogenic carbonate deposits in relation to the initial δ18O, δ13CDIC and chemical composition of the water from which it precipitated. This study focuses on cryogenic calcites precipitated in relation to aufeis aggradation since it offers the possibility of examining the chemical and isotopic partitioning that occurs during freezing. The studied aufeis are located in the western Canadian Arctic (YT and NWT), a region underlain mostly by limestone bedrock, and southern Baffin Island (NU), an area of crystalline bedrock. The results indicate that the δ18O composition of cryogenic calcite from a carbonated environment are slightly depleted over that of the initial δ18O of the parent water, while those from a non-carbonated environment are strongly depleted over the initial δ18O of the parent water as a result of the lower calcite saturation state of the parent water. This suggest that the δ18O of cryogenic carbonates not only depends on the initial δ18O composition of the parent water and the temperature at which the carbonate precipitated, but also on the calcite saturation state of the parent water and kinetic inhibitions during calcite precipitation. Given that the aggradation of aufeis occurs under closed-system freezing, the residual water will become progressively depleted in δ18O as a result of the removal of heavier isotopes in the ice. In addition, freezing imparts a concentration of solutes in the residual water, which leads to an increase in calcite saturation index. Therefore, carbonate precipitated in equilibrium from water that has a low calcite saturation index will have a highly depleted δ18O composition over that of the initial δ18O values of the parent water since the calcite saturation state will only be exceeded in the late stage of freezing. By contrast, solute and isotopic partitioning during freezing has little effect on the δ13C of the cryogenic carbonates as it tends to reflect that of the initial δ13CDIC value of the parent water. These findings have significant implications in the use of cryogenic carbonates in paleoclimate studies. Care must be taken when interpreting the δ18O signature preserved in cryogenic carbonates since their signature might be modified by freezing prior to their precipitation, which will lead to a lighter δ18O composition of the cryogenic carbonates. Therefore, it would be difficult to use the δ18O composition of cryogenic carbonates as a direct proxy in paleoclimatic reconstruction unless details about the chemical composition of parent waters are known. Nevertheless, the δ13C composition of the cryogenic carbonates that precipitated under closed-system conditions can allow insights into the different water sources contributing to carbonate precipitation. © 2006 Elsevier B.V. All rights reserved.
Keywords: AUFEIS; CANADIAN ARCTIC; CRYOGENIC CARBONATES; NORTHERN YUKON TERRITORY; SOUTHERN BAFFIN ISLAND; STABLE ISOTOPES OF CARBON; STABLE ISOTOPES OF OXYGEN